Development and validation of risk prediction equations to estimate future risk of heart failure in patients with diabetes: a prospective cohort study - Hippisley-Cox, Julia; Coupland, Carol (BMJ Publishing Group Ltd, 2015)
Objective: To develop and externally validate risk prediction equations to estimate the 10-year risk of heart failure in patients with diabetes, aged 25–84 years.